Collision-driven state-changing efficiency of different buffer gases in cold traps: He(1S), Ar(1S) and p-H2(1Σ) on trapped CN−(1Σ). Issue 13 (17th August 2020) - González-Sánchez, Lola; Yurtsever, Ersin; Mant, Barry P.; Wester, Roland; Gianturco, Franco A.
Abstract : Views of quantum potentials for CN − with He and Ar. Dynamics of the anion's rotational state-changes models cooling kinetics for either buffer gases in cold traps. Abstract : We employ potential energy surfaces (PES) from ab initio quantum chemistry methods to describe the interaction of the CN − ( 1 Σ) molecule, one of the small anions often studied at low temperatures, with other possible gases which can be employed as buffer in cold ion traps: the He and Ar atoms and the p-H2 molecule. These PESs are used to calculate from quantum multichannel dynamics the corresponding state-changing rate constants between the populated rotational states of the anion, the latter being in its electronic and vibrational ground states. The different cross sections for the collision-driven quenching and excitation processes at low temperatures are compared and further used to model CN − cooling (de-excitation) efficiency under different trap conditions. The interplay of potential coupling strength and mass-scaling effects is discussed to explain the differences of behaviour among the buffer gases. The advantages of being able to perform collisional cooling at higher trap temperatures when using Ar and p-H2 as buffer gases are also discussed.